A CRITICAL APPRAISAL ON IMMUNOMODULATION AND BATTLE AGAINST COVID-19: AN EVIDENCE BASED PREVENTIVE AYURVEDIC APPROACH (AYUSHDHARA, 2020)
The emergence of SARSCOV-2 has been noticed as the third introduction of a highly pathogenic corona virus into the human population after SARS-COV and MERV-COV in 21st century. It has posed a horrible situation that warrants urgent global attention due to the emergence of more virulent viral strain, predicted future viral mutations, prohibitive cost of available drugs, time lag between vaccine development and mass causalities occurring all over the world. Although specific antiviral vaccine is the effective solution but a potent and comprehensive immune response to maintain homeostasis is also critical for prophylactic as well as therapeutic management of the disease. Amidst all the gloom spread due to this outbreak, everyone is focusing on preventive measures until an effective vaccine is developed. Ayurveda- An holistic science offers a plethora of preventive therapies to enhance body’s resistance against infections. It is evident that nutritional and herbal approaches taken together provide potent tools for controlling an array of viral infections and have been effectively used by humans all over the world since ages during such outbreaks. Ayurveda and yoga have great potential for embracing the world in creating a more positive health abode. Herbs exhibit a diverse array of biological activities and can be effectively harnessed for managing this pandemic. This review portrays an eclectic overview for the preventive management of COVID-19 pandemic covering the dietary, lifestyle and herbal evidence based approaches that may be most likely helpful in managing the current pandemic scenario and also strengthens our body to cope-up with the next pandemic that might appear in not too distant future.